Floral Diversity along Sub-alpine and Alpine Ecosystems in Tungnath Area of Kedarnath Wildlife Sanctuary, Uttarakhand - Rai, Ishwari D.; Adhikari, Bhupendra S.; Rawat, Gopal S. (Indian Forester, 2012)
Extensive floristic surveys were carried out at Tungnath area in Kedarnath Wildlife Sanctuary during 2007-2011. During the survey a total of 433 plant species belonging to 234 genera under 71 families were recorded along the sub-alpine and alpine region (2800-3680m amsl). Of which 349, 42, 18, 13, 5, 6 and species were herbs, shrubs, grasses, trees, sedges and climbers, respectively. Among dicotyledonous families Asteraceae was the largest family represented by 42 species followed by Rosaceae (30 species), Ranunculaceae (25 species), Polygonaceae (24 species), Scrophulariaceae (17 species) and Apiaceae (17 species), whereas Orchidaceae (29 species), Poaceae (19 species) and Liliaceae (13 species) were the major families among the monocotyledons. Some uncommon species viz., Balanophora involucrata, Cypripedium spp., Calanthe manii and Eleutherococcus cissifolius were recorded for the first time from the area. The species categorised under various threat categories (rare, endangered and threatened) e.g., Cyananthus integer, Dactylorhiza hatagirea, Balanophora involucrata, Fritillaria roylei, Jurinea macrocephala were also recorded during the survey.